2014
DOI: 10.1007/s11255-014-0785-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effects of intraoperative human albumin and normal saline on early graft function in renal transplantation

Abstract: This study revealed that the use of 20 % human albumin as an intraoperative volume expander provides no more benefit than the use of 0.9 % normal saline in terms of immediate graft function in living donor renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…11,12 Colloids too have been studied, but with inconclusive results. [13][14][15] Irrespective of fluid type, adequate perfusion of the renal allograft is important to reduce DGF risk; hence, many anesthesiologists favor liberal administration of fluids during kidney transplantation, 16 despite inconclusive evidence to support this practice. 5,6,10,17 The RELIEF trial examined a restrictive versus liberal fluid strategy in 3000 patients undergoing major abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Colloids too have been studied, but with inconclusive results. [13][14][15] Irrespective of fluid type, adequate perfusion of the renal allograft is important to reduce DGF risk; hence, many anesthesiologists favor liberal administration of fluids during kidney transplantation, 16 despite inconclusive evidence to support this practice. 5,6,10,17 The RELIEF trial examined a restrictive versus liberal fluid strategy in 3000 patients undergoing major abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The geriatric nutritional risk index (GNRI) was developed as a simple and objective nutritional assessment tool for hospitalized elderly patients (aged ≄ 65 years, according to World Health Organization definition of elderly; https://www.who.int/) based on their body weight and serum albumin level [5]. Albumin is affected by agerelated changes such as hydration and hepatic and renal dysfunction [6][7][8]. In addition, body weight appears to be a good indicator of both the severity of systemic illness and the amount of protein-calorie stores [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective randomized trial of 20% human albumin + 0.9% saline versus 0.9 % saline alone in LDKT recipients, there were no differences in the graft outcome. 35 A similar study (80 LDKT recipients), also using 20% albumin, also found no differences in graft function, although no patient had delayed graft function requiring dialysis. 36 A recent study evaluated kidneys from deceased donors (after neurological death) who received colloid (primarily gelatin [68%], less frequently albumin [17%], and starch [17%]) with crystalloid compared to crystalloid alone (data for 143/181 transplanted kidneys from 100 donors).…”
Section: Albuminmentioning
confidence: 78%